Molecular Genetic Markers and Clinical Characteristics of Essential Thrombocythemia - AA Zhernyakova (Kliničeskaâ onkogematologiâ, 2017)
Background & Aims. The presence of different molecular genetic markers of clonality (mutations in JAK2, MPL, CALR) or their absence (triple negative status, TN) in essential thrombocythemia (ET) indicates a biological heterogeneity of the disease and can determine its clinical forms. The aim was to evaluate the association of molecular genetic markers with the clinical form and the prognosis of ET.